Corrosion of 3D-Printed AlSi9Cu3Fe Alloy - Fousova, Michaela; Valesova, Veronika; Vojtech, Dalibor (Manufacturing Technology Journal, 2019)
Although 3D printing offers many advantages over casting, it can alter the corrosion behaviour of processed metals and alloys. The corrosion behaviour is related primarily to the microstructure, which is very fine and heterogeneous in 3D printed metals due to very high cooling rates and the additive way of manufacture layer by layer. Therefore, we carried out corrosion tests according to the Audi internal standard to demonstrate how the 3D printing process influenced the corrosion behaviour of the AlSi9Cu3Fe alloy prepared by selective laser melting compared to a conventional casting. Corrosion rates were determined from mass losses and corrosion attacks were documented microscopically. Compared to the cast material, the corrosion rate was increased by ~ 60 % after 3D printing. Related to the microstructural heterogeneity and anisotropy, an uneven attack was observed on different sides of the tested samples.
Keywords: AlSi9Cu3Fe; corrosion; 3D printing